Genesis of Neruda's poetry book Hřbitovní kvítí - Mocná, Dagmar (Bohemica Olomucensia, 2012)
The paper attempts the new reading of one well-known Neruda's work that belongs to the canon of Czech literature, even though its exegets do not hide their embarrassments if that book has got an undeniable value or not. The paper contributes to the latent discussion about the book and suggests the esthetical norms of the 19th century, when the Neruda's work was written, and reconstructs genesis of Hřbitovní kvítí.